Screening of factors affecting the enzymatic hydrolysis of fiber pressed palm frond (FPOPF) - Nur Fatin, Muhammad (2015)
This paper reviews the alkaline pretreatment and factors that affecting the enzymatic hydrolysis oil palm frond (OPF). The factors studied in enzymatic hydrolysis are enzyme concentration, pH, temperature, reaction time and agitation speed. OPF is one type of agricultural wastes that consist of lignocellulosic material which comprised of cellulose, hemicellulose and lignin. Lignin is extremely strong component which resistant against chemical, enzymatic and bacteria breakdown. Thus, usage of lignocellulosic as a raw material involves alkaline pretreatment to be able to make the cellulose and hemicellulose fractions easily accessible for enzymatic hydrolysis. Dried OPF was pretreated by soaking into sodium hydroxide solution at 100°C for about 1 hour. For hydrolysis, the pretreated OPF was soaked into sodium acetate buffer and enzyme was applied too. The, the mixture was incubated in an incubator shaker. After that, the mixture was boiled in water bath for 10 minutes. The hydrolysates were quantified by using DNS method. After analyzed with Design Expert Software, pH gives the most contribution to the enzymatic hydrolysis. Lignocellulose material is known as a potential biomass for conversion into renewable sugar to produce value-added product such as biofuels, animal feeds, enzyme and healthy food products.